Digital Literacy Skills in Improving the Performance of MSMEs in Indonesia : A Systematic Literature Review - Oktavianti, Indira; Budi Eko Soetjipto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Digital literacy at the Micro, Small and Medium Enterprises (MSME) scale is part of the digital transformation that can drive economic growth in Indonesia. Business actors are required to have digital skills, one of the important aspects to build a sustainable strategy as a form of solution for business people in an effort to develop their business. This research aims to explore the understanding of digital literacy among Indonesian MSMEs, focusing on the development of digital transformation, digital adoption, challenges and obstacles, and strategies used for business sustainability. The method used in this research is Systematic Literature Review (SLR) with stages: planning, implementation, and reporting. SLR in this study was conducted using a collection of literature studies published from January 2020 to October 2024. The results of this study indicate that digital literacy is an important factor affecting performance among MSMEs, through skills in utilizing digital platform opportunities in the context of business development such as e-commerce platforms. Challenges faced such as limited resources in managing technological devices and lack of digital literacy can be overcome by implementing strategies to improve skills and understanding related to digitalization, fostering a supportive ecosystem, and socializing the importance of entrepreneurial leadership optimally to achieve sustainable growth and higher competitiveness.